Invariant NKT cell response to dengue virus infection in human. - Ponpan Matangkasombut; Wilawan Chan-In; Anunya Opasawaschai; Pisut Pongchaikul; Nattaya Tangthawornchaikul; Sirijitt Vasanawathana; Wannee Limpitikul; Prida Malasit; Thaneeya Duangchinda; Gavin Screaton; Juthathip Mongkolsapaya (PLoS Neglected Tropical Diseases)
Background Dengue viral infection is a global health threat without vaccine or specific treatment. The clinical outcome varies from asymptomatic, mild dengue fever (DF) to severe dengue hemorrhagic fever (DHF). While adaptive immune responses were found to be detrimental in the dengue pathogenesis, the roles of earlier innate events remain largely uninvestigated. Invariant natural killer T (iNKT) cells represent innate-like T cells that could dictate subsequent adaptive response but their role in human dengue virus infection is not known. We hypothesized that iNKT cells play a role in human dengue infection. Methods Blood samples from a well-characterized cohort of children with DF, DHF, in comparison to non-dengue febrile illness (OFI) and healthy controls at various time points were studied. iNKT cells activation were analyzed by the expression of CD69 by flow cytometry. Their cytokine production was then analyzed after α-GalCer stimulation. Further, the CD1d expression on monocytes, and CD69 expression on conventional T cells were measured. Results iNKT cells were activated during acute dengue infection. The level of iNKT cell activation associates with the disease severity. Furthermore, these iNKT cells had altered functional response to subsequent ex vivo stimulation with α-GalCer. Moreover, during acute dengue infection, monocytic CD1d expression was also upregulated and conventional T cells also became activated. Conclusion iNKT cells might play an early and critical role in the pathogenesis of severe dengue viral infection in human. Targeting iNKT cells and CD1d serve as a potential therapeutic strategy for severe dengue infection in the future.